Velocity field estimation on density-driven solute transport with a convolutional neural network [dataset] - Kreyenberg, Philipp J.; Bauser, Hannes; Roth, Kurt (Universität, 2019)
This data set accompanies the manuscript ‘Velocity Field Estimation on Density-Driven Solute Transport With a Convolutional Neural Network’. Concen...
Gesehen am 21.05.2019
Keywords: Forschungsdaten; Datenbank